Woman in the Shadow of Sirri Polygamy in Masbagik District, West Nusa Tenggara: A Legal and Psychological Analysis of the Loss in Inheritance Rights - Utami, Gita; Murdan, Murdan (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
The practice of unregistered marriage is no longer a strange thing in community life. Unregistered marriage or so-called underhand marriage or unregistered marriage is a marriage that is carried out legally according to Islamic law but is not registered administratively by the state. Although the provisions of the law have expressly regulated the requirement for marriage to be registered by authorized officials, the practice of unregistered marriage is still widespread. Unregistered marriages have quite serious impacts. Not only problems in the legal field, but also include the social, economis, and psychological aspects of the perpetrators. The purpose of this study was to determine 1) the legal position of wives who are polygamized unregistered; 2) the psychological impact of wives who do not receive inheritance rights due to unregistered polygamy. In discussing the problems contained in this study, the approaches used are normative legal and empirical legal approaches. Based on the results of the discussion, the position of the wife in unregistered polygamy is a legal wife according to religion, but because the marriage is not registered at the KUA, then according to the applicable positive law, the marriage does not have legal force so that the consequences is that the marriage cannot have legal consequences. The loss of inheritance rights due to an unregistered marriage has a major impact on a wifes psychological condition. [Praktik perkawinan sirri menjadi hal yang tidak asing lagi dalam kehidupan bermasyarakat. Kawin sirri atau disebut kawin di bawah tangan atau kawin tidak tercatat adalah perkawinan yang dilakukan sah menurut syariat Islam namuj tidak dicatatatkan secara administrasi negara. Meskipun ketentuan perundang-undangan telah secara tegas mengatur keharusan perkawinan untuk dicatatkan oleh pejabat yang berwenang, namun praktik perkawinan sirri masih marak terjadi. Perkawinan yang tidak dicatatkan menimbulkan dampak yang cukup serius. Tidak hanya permasalahan pada bidang hukum, tetapi juga meliputi sosial, ekonomi, dan psikologis pelakunya. Tujuan penelitian ini adalah untuk mengetahui 1) kedudukan hukum istri yang di poligami secara sirri; 2) dampak psikologis istri yang tidak mendapatkan hak waris akibat di poligami secara sirri Dalam membahas permasalahan yang terdapat dalam penelitian ini, pendekatan yang digunakan, yaitu pendekatan secara yuridis normatif dan yuridis empiris. Berdasarkan hasil pembahasan, kedudukan istri dalam poligami sirri adalah istri sah secara agama namun oleh karena perkawinan tersebut tidak dicatatkan di KUA, maka secara hukum positif yang berlaku, perkawinan tersebut tidak memiliki kekuatan hukum sehingga konsekuensinya yaitu perkawinan tersebut tidak dapat menimbulkan akibat hukum. Hilangnya hak waris akibat perkawinan yang tidak tercatat sangat berdampak terhadap kondisi psikologis seorang istri].